ZONASI MINI MARKET DI KOTA PALOPO SUATU UPAYA PERLINDUNGAN PASAR TRADISIONAL DAN WARUNG KECIL - Abd. Kadir Arno; Nur Ariani Aqidah (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2018)
Regional Regulation Number 9 of 2012 on the Spatial Planning of the City of Palopo became a reference in the zoning of minimarkets in Palopo City as a form of implementation and implementation of Presidential Regulation Number 112 of 2007 about Arrangement and Development of Traditional Markets, Shopping Centers and Modern Shops, in regulating permits from the establishment of Minimarkets in Palopo City. At present the Palopo City Government only gives establishment permits based on regional zoning in 5 sub-districts from 9 sub-districts in Palopo City